Estudo do processo de remoção de microalgas para obtenção de água potável - Moreti, Livia de Oliveira Ruiz (2014)
This study aims to evaluate the efficiency of coagulantion/floculation/dissolved air flotation (C/F/DAF) using Moringa oleifera powder seeds as natural coagulant for cyanobacterial cells removal and subsequent lipid characterization of sludge generated. For the test, it was used "synthetic water", using culture médium ASM-1 containing cyanobacterial cells and diluted in deionized water, artificially contaminated with Anabaena flos-aquae cells, for cell density in the order of 104 cells.mL-1, simulating a bloom. Another culture was also performed, this time using as inoculum precursor, Chlorella vulgaris cells, was used culture medium BG-11, in which was obtained a cell density on the order of 10-6 células.mL-1. This work was realized in three steps: 1) Optimization the operating conditions in the C/F/FAD step, related to mixing flotation parameters process, based on the percentage reduction of the parameters apparent color, turbidity and chlorophyll-a; 2) Evaluation of Moringa oleifera Lam coagulant optimal dosage, based on the percentage reduction in parameters apparent color, turbidity and chlorophyll-a and absorption compounds at UV254nm; 3) Characterization of lipid produced by specie of cyanobacteria (Anabaena flos-aquae) compared to a specie of green algae (Chlorella vulgaris). It was found that mixing and flotation parameters affect the removal efficiency of the evaluated parameters and the optimal operating conditions were: fast mixing gradient (FMG) 850 s-1, fast mixing time (FMT) of 20 s, slow mixing gradient (SMG) at 15 s-1, slow mixing time (SMT) of 20 min and pressure of 600 kPa, saturation time of 4 minutes, flotation velocity of 10 cm.min-1 and recirculation rate of 30% for FAD. The optimum dosage of coagulant was 0.1 g.L-1, reaching removal percentages of color, turbidity, chlorophyll-a and absorption compounds at UV254nm in the order of 80.5; 78.1; 96.4 and 39.1%, respectively. Regarding the fatty acids profile present in Anabaena flos-aquae profile and Chlorella vulgaris without treatment with Moringa, it was found that the satured fatty acids corresponding to 40.4% and 35.58%, respectively. For A. flos-aquae it was observed that the highest composition percentage was assigned to palmitic acid (C16:0), with a value of 30.55%, followed by linoleic acid (C18:2n6), with 17% and oleic acid (C18:1n9), with 7.4%. Already for C. vulgaris, the highest composition percentage was assigned to araquidic acid (C20:0), with a value of 21.15%, oleic acid (C18:1n9:0) with 18.85% and followed by palmitic acid (C16:0) and oleic acid (C18:1n9) about 15% each. After Moringa treatment, it can be observed that both species showed most compounds composed by unsaturated fatty acids, 66.9% to Anabaena and 71.1% to Chlorella, and among these, stood out oleic acid with 61.7 and 69.5%, respectively. Thus, it can conclude that the water treatment process, C/F/FAD using Moringa powder seeds, was efficient in removing cyanobacteria cells, apparent color and turbidity beyond to produce a rich sludge with oleic acid, that can be an alternative source for biodiesel production.